The Essence and Approaches to the Interpretation of Law in the Works of Domestic Scholars - V. K. Antoshkina (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The legal theory of interpretation was the subject of study and research by legal scholars, both practitioners and theoreticians for centuries. Despite the fact that this scientific work allows us to outline the basic approaches to determining the components of the interpretation theory, its study does not stop today, because of the rapid development of society, the emergence of new types and varieties of relations, all spheres of life globalization of sets new challenges, including to the jurists. All these factors make it necessary to reconsider the established approaches, to adapt to new conditions of being, which is quite characteristic of the law interpretation practice. That paper is aimed at identifying approaches to the essence and concept of legal interpretation as a complex, multi-faceted process, taking into account the achievements of national science. The aim is offered to be realized through the fulfillment of the following tasks: highlighting and analysis of the basic approaches, established in the national legal science to law interpretation practice in recent decades and outlining directions of further scientific research in this field. It will provide a comprehensive approach to determining the main characteristics and nature of the law interpretation process at the present stage. To achieve that goal, the author used methods of analysis and synthesis to reflect the unity and difference of views on the phenomenon of the study, and also used a comparative legal method and a systematic one.The author outlined the material in chronological order on the topics of scientific works, their main directions, indicating the main views on the nature of legal interpretation or its individual components. The article demonstrates the way the definition of law interpretation activity has changed, evolved and modernized.We can conclude that the issues that are of most interest of domestic law researchers are concepts and purpose, subjects and objects of interpretation, principles, boundaries, means, rules, results, philosophical foundations of law interpretation activity, features of interpretation depending on the sphere of law characteristics. At the same time, there are promising scientific researches in the mentioned field of law and philology, philosophy, as well as reconsidering the theory of interpretation within certain spheres of law.It should be noted that some ideas about amending the rules and methods of interpretation expressed by scholars in the works are reflected in the current legislation, but, at the same time, that process is not systematic, so it is necessary to step up efforts in the mentioned direction.